Efektivitas Program Sistem Informasi Kesejahteraan Sosial (SIKS-Ng) dalam Mendukung Program SLRT dan Puskesos Dinas Sosial Provinsi Sulawesi Selatan - Asrandi T, Andi Muhammad; Wati, Sari Apriliya; Wahab, Abdul; Alfian, Alfian (CV. Publikasi Indonesia, 2022)
Poverty in South Sulawesi Province has experienced a significant decline with a rate of 1.01% from 2016 to 2018, where this decline is in line with the implementation of an Integrated Social Protection System called